Visual skills of elite Brazilian football players - Alves, M.; Spaniol, F.; Erichsen, O. (European Journal of Sports & Exercise Science, 2015)
Several authors have reported the importance of visual skills (or sports vision) for sport performance, however, little has been investigated about visual skills of football players. Thus, the purpose of the study was to investigate the visual skills of elite Brazilian football players and compare visual skills scores of players from different age groups and different positions. Fifty male elite Brazilian football players from a top football club from the main Brazilian football league (first division) performed the visual skills test using Vizual EdgePerformance Trainer® (VEPT) for the following visual skills: eye alignment, depth perception, convergence, divergence, visual recognition, and visual tracking.No statistical significance was found between the age groups for eye alignment, depth perception, convergence, divergence, visual recognition, and VEPT (combined total score) scores. Conversely, statistical significance was found for visual tracking, in which the Pro (93.4 ± 2.2 %, P=0.05) and U20 (95.2 ± 1.8 %, P=0.00) were significantly better than the U15 (85.9 ± 1.8 %). In addition, the U20 (95.2 ± 1.8 %, P=0.03) was also significantly better than the U17 (87.2 ± 2.1 %). With regards to players of different positions (goalkeepers, defenders, midfielders and forwards), no statistical significance was found for any of the variables tested. In conclusion, the present study reports that the visual skills, more specifically visual tracking, of more developed and experienced elite football players (U20 and main squad) are greater than the visual skills of younger and less experienced elite football players (U15 and U17).